Validation of the deck behaviour due to post-tension loading of Ashton arch bridge - Van Wijk, Heinrich (Department of Civil Engineering, 2020)
The new Ashton Bridge is a concrete tied-arch structure with a cable-supported deck, which spans 110 metres below the arching ribs. The tie-beam members, connecting the arch ribs, each have six longitudinal tendons that have primarily straight profiles. The author set out to validate the structural behaviour of the tie-beams, after the post-tensioning construction stage. This objective was achieved by validating selected finite element model parameters with field conducted tests. The input parameter, which is the prestress loading onto the structure, was validated with tendon elongation measurements and tendon lift-off tests. The output parameter, which is the strain and displacement response of the structure, was verified by measuring the elastic deck shortening and the strain gauge readings. Lower tendon extensions were encountered during tensioning. This required calibration of the friction coefficients and model updating. Lift-off tests and deck shortening measurements provided and order size estimation of the structural behaviour, but was not adequate for model validation. The strain gauge readings showed a close correlation with the expected strain state of the structure and offered insight into the behaviour of the structure during post-tensioning. The methods described in this dissertation may be used for validating the structural behaviour of concrete bridges subject to post-tensioning. Suggestions for improving tendon lift-off tests and deck shortening measurements are also presented.